Status of teachers of business subjects in the secondary schools of Kansas. 1953-1954. - Turnover of business teachers in the secondary schools of Kansas, 1952-1953 by B.L. Fowler. - List of free teaching aids for typing, bookkeeping and shorthand by E.P. Evans (Kansas State Teachers College, 1954)
In: The Emporia State Research Studies 3(1954) 1.